Capitalism 3.0 : a guide to reclaiming the commons - Barnes, Peter (Berrett-Koehler Publishers, 2006)
The commons - those creations of nature and society we inherit together and must preserve for our children - is under siege. Our current version of capitalism - the corporate, globalized version 2.0 - is rapidly squandering this heritage. Now, Peter Barnes offers a solution: protect the commons by giving it property rights and strong institutional managers. Barnes shows how capitalism - like a computer - is run by an operating system. Our current operating system gives too much power to profit-maximizing corporations that devour the commons and distribute most of their profits to a sliver of the population.